2006
DOI: 10.1098/rstb.2006.1928
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and mechanisms of genetic and phenotypic differentiation in marine microbes

Abstract: Microbes in the ocean dominate biogeochemical processes and are far more diverse than anticipated. Thus, in order to understand the ocean system, we need to delineate microbial populations with predictable ecological functions. Recent observations suggest that ocean communities comprise diverse groups of bacteria organized into genotypic (and phenotypic) clusters of closely related organisms. Although such patterns are similar to metazoan communities, the underlying mechanisms for microbial communities may dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(170 citation statements)
references
References 112 publications
11
156
0
1
Order By: Relevance
“…Previous studies indicate that such microdiversity clusters could represent important units of differentiation as ecotypes in natural populations of bacteria (Palys et al, 1997;Moore et al, 1998;Rocap et al, 2003;Konstantinidis and Tiedje, 2005;Lopez-Lopez et al, 2005;Thompson et al, 2005;Cohan, 2006;Polz et al, 2006;Cohan and Perry, 2007), and are often observed in environmental clone libraries (Field et al, 1997;Acinas et al, 2004;Morris et al, 2005;Johnson et al, 2006;Pommier et al, 2007). The microdiversity clusters identified here are correlated with morphological and ecophysiological traits such as cell length and the capacity to perform CCA (Figures 4 and 5), providing further support for the designation as an ecotype (Ahlgren and Rocap, 2006;Johnson et al, 2006;Polz et al, 2006;Ward et al, 2006). Although this genetic pattern agrees with the ecotype model for bacterial species (Palys et al, 1997;Cohan, 2002;Gevers et al, 2005;Cohan and Perry, 2007), other mechanisms causing the genetic diversification of Pseudanabaena populations cannot be excluded.…”
Section: Genetic Diversification Of Pseudanabaena Populationsmentioning
confidence: 57%
“…Previous studies indicate that such microdiversity clusters could represent important units of differentiation as ecotypes in natural populations of bacteria (Palys et al, 1997;Moore et al, 1998;Rocap et al, 2003;Konstantinidis and Tiedje, 2005;Lopez-Lopez et al, 2005;Thompson et al, 2005;Cohan, 2006;Polz et al, 2006;Cohan and Perry, 2007), and are often observed in environmental clone libraries (Field et al, 1997;Acinas et al, 2004;Morris et al, 2005;Johnson et al, 2006;Pommier et al, 2007). The microdiversity clusters identified here are correlated with morphological and ecophysiological traits such as cell length and the capacity to perform CCA (Figures 4 and 5), providing further support for the designation as an ecotype (Ahlgren and Rocap, 2006;Johnson et al, 2006;Polz et al, 2006;Ward et al, 2006). Although this genetic pattern agrees with the ecotype model for bacterial species (Palys et al, 1997;Cohan, 2002;Gevers et al, 2005;Cohan and Perry, 2007), other mechanisms causing the genetic diversification of Pseudanabaena populations cannot be excluded.…”
Section: Genetic Diversification Of Pseudanabaena Populationsmentioning
confidence: 57%
“…Also, given that they are halotolerant (rather than halophilic), psychrotolerant (rather than psychrophilic), and metabolically versatile indicates that they are flexible in their response to water potential, temperature, and nutrient availability. Therefore, given the evidence available so far, our working model for why Naganishia species are so prevalent on these high elevation volcanoes is that they are flexible “opportunitrophs” ( cf Polz et al 2006; Westrich et al 2016) that can grow during rare periods of water (from melting snow) and nutrient availability (from Aeolian inputs). However, much more work is needed to verify that Naganishia species are actually functioning in these high elevation soils (and at similar sites in Antarctica) and to understand how they are dispersed through the atmosphere to remote sites throughout the cryosphere.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, N. friedmannii and N. consortionis from Antarctica used 48 and 30% of the same 27 organic compounds, respectively (Barnett et al 2000), perhaps indicating that the Antarctic isolates have a narrower metabolic niche than the Llullaillaco isolate. The metabolic versatility of the Llullaillaco isolate may indicate that this organism is an opportunitroph as defined by Polz et al (2006), that is, an organism capable of “exploiting spatially and temporally variable resources”. Many of the substrates used for growth by this organism are plant-derived compounds (e.g.…”
Section: Ecological Tolerances Of Naganishiamentioning
confidence: 98%
“…These considerations are relevant for microbial communities since they are typically sampled at the 'bucket' scale, corresponding more to ecosystem rather than to habitat scales, and with phylogenetic markers (for example, 16S rRNA genes) that have relatively coarse genotypic resolution. The latter is particularly important for microbes since horizontal gene transfer can spread adaptive genes rapidly so that slowly evolving marker genes may not provide sufficient resolution to differentiate at the population level (Doolittle and Papke, 2006;Polz et al, 2006). We therefore suggest that fine spatial and, in particular for aquatic microbes, temporal scale comparative sampling will be important to clarify whether bacterioplankton generally assembles with high niche fidelity and thus according to 'rules.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, metagenomic comparison has revealed similar metabolic functions in phylogenetically distant microbes (Venter et al, 2004;Howard et al, 2008;Mou et al, 2008) suggesting that these might be, to a high degree, functionally interchangeable. Taken together, these results pose serious challenges for interpretation of community structure and dynamics (Polz et al, 2006). A key question is to what extent microbes are optimized for, and therefore linked to, specific ecological opportunities and to what extent they tend to act as ecological generalists.…”
Section: Introductionmentioning
confidence: 99%